2003
DOI: 10.1212/01.wnl.0000090462.62087.a1
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s encephalopathy

Abstract: The clinical features of Hashimoto's encephalopathy have been attributed to a cerebral vasculitis, but pathologic material is rarely available. The authors describe an individual with Hashimoto's encephalopathy complicated by fatal status epilepticus. Postmortem examination demonstrated mild perivascular lymphocytic infiltration throughout the brain and leptomeninges plus diffuse gliosis of gray matter in the cortex, basal ganglia, thalami, hippocampi, and, to a lesser extent, the parenchymal white matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 4 publications
0
59
0
1
Order By: Relevance
“…Hadjivassiliou (29,30), thrombotic thrombocytopenic purpura (31) and ChurgStrauss syndrome (32) (2,33,34). Furthermore, SPECT studies have reported abnormal cerebral perfusion in celiac disease (35) and Hashimoto's thyroiditis with normal thyroid function (36 …”
Section: Selim and Drachman Reported That Two Of Six Patients With Anmentioning
confidence: 99%
“…Hadjivassiliou (29,30), thrombotic thrombocytopenic purpura (31) and ChurgStrauss syndrome (32) (2,33,34). Furthermore, SPECT studies have reported abnormal cerebral perfusion in celiac disease (35) and Hashimoto's thyroiditis with normal thyroid function (36 …”
Section: Selim and Drachman Reported That Two Of Six Patients With Anmentioning
confidence: 99%
“…Most evidence suggests an auto-immune vasculitis or other immune-mediated process affecting the cerebral microvasculature. Post-mortem studies of some individuals have shown lymphocytic vasculitis of venules and veins in the brain stem and a diffuse gliosis involving gray matter more than white matter [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…One possible pathologic mechanism of HE is the involvement of an autoimmune inflammatory process because pathological findings of brain biopsy specimens have revealed marked lymphocytic infiltration of parenchymal arterioles and venules (3). Furthermore, in one patient with HE, the autopsy findings demonstrated lymphocytic infiltration throughout the walls of arterioles and venules in the brain stem, white matter, cortex and leptomeninges (4).…”
Section: A C B D E Fmentioning
confidence: 92%
“…Although autoimmune mechanisms may underlie the pathogenesis, the precise cause of HE remains unclear. Autoimmune cerebral vasculitis is likely because neuropathological examinations of biopsy and autopsy specimens have shown lymphocytic infiltration into the walls of arterioles and venules in brain parenchyma (3,4) and leptomeninges (4). Recently, Yoneda and colleagues reported that serum autoantibodies against the N-terminal region of α-enolase (NAE) are a useful diagnostic marker for HE (5).…”
Section: Introductionmentioning
confidence: 99%